Chronic Effects of Static Stretching Exercises on Skeletal Muscle Hypertrophy in Healthy Individuals: A Systematic Review and Multilevel Meta-Analysis - Fabian Arntz; Adrian Markov; Brad J. Schoenfeld; Martin Behrens; David G. Behm; Olaf Prieske; Yassine Negra; Helmi Chaabene (SpringerOpen, 2024)
Abstract Background The chronic effect of static stretching (SS) on muscle hypertrophy is still unclear. This study aimed to examine the chronic effects of SS exercises on skeletal muscle hypertrophy in healthy individuals. Methods A systematic literature search was conducted in the PubMed, Web of Science, Cochrane Library, and SPORTDiscus databases up to July 2023. Included studies examined chronic effects of SS exercise compared to an active/passive control group or the contralateral leg (i.e., utilizing between- or within-study designs, respectively) and assessed at least one outcome of skeletal muscle hypertrophy in healthy individuals with no age restriction. Results Twenty-five studies met the inclusion criteria. Overall, findings indicated an unclear effect of chronic SS exercises on skeletal muscle hypertrophy with a trivial point estimate (standardised mean difference [SMD] = 0.118 [95% prediction interval [95% PI] = − 0.233 to 0.469; p = 0.017]) and low heterogeneity (I2 = 24%). Subgroup analyses revealed that trained individuals (β = 0.424; 95% PI = 0.095 to 0.753) displayed larger effects compared to recreationally trained (β = 0.115; 95% PI = − 0.195 to 0.425) and sedentary individuals (β = − 0.081; 95% PI = − 0.399 to 0.236). Subanalysis suggested the potential for greater skeletal muscle hypertrophy in samples with higher percentages of females (β = 0.003, [95% confidence interval [95% CI] = − 0.000 to 0.005]). However, the practical significance of this finding is questionable. Furthermore, a greater variety of stretching exercises elicited larger increases in muscle hypertrophy (β = 0.069, [95% CI = 0.041 to 0.097]). Longer durations of single stretching exercises (β = 0.006, [95% CI = 0.002 to 0.010]), time under stretching per session (β = 0.006, [95% CI = 0.003 to 0.009]), per week (β = 0.001, [95% CI = 0.000 to 0.001]) and in total (β = 0.008, [95% CI = 0.003 to 0.013]) induced larger muscle hypertrophy. Regarding joint range of motion, there was a clear positive effect with a moderate point estimate (β = 0.698; 95% PI = 0.147 to 1.249; p < 0.001) and moderate heterogeneity (I2 = 43%). Moreover, findings indicated no significant association between the gains in joint range of motion and the increase in muscle hypertrophy (β = 0.036, [95% CI = − 0.123 to 0.196]; p = 0.638). Conclusions This study revealed an overall unclear chronic effect of SS on skeletal muscle hypertrophy, although interpretation across the range of PI suggests a potential modest beneficial effect. Subgroup analysis indicated larger stretching-induced muscle gains in trained individuals, a more varied selection of SS exercises, longer mean duration of single stretching exercise, increased time under SS per session, week, and in total, and possibly in samples with a higher proportion of females. From a practical perspective, it appears that SS exercises may not be highly effective in promoting skeletal muscle hypertrophy unless a higher duration of training is utilized. PROSPERO registration number: CRD42022331762.